The heterotrimeric G protein г Stgg1 is required for conidiation, secondary metabolite production and pathogenicity of Setosphaeria turcica - Pan Li; Xinjie Zhang; Yibin Lin; Shen Shen; Yulan Zhao; Jingao Dong; Zhimin Hao (Biotechnology & Biotechnological Equipment, 2018)
Heterotrimeric G proteins are best known for their role in the transduction of extracellular signals to various downstream effectors. G proteins in higher eukaryotes are intensively studied; however, their roles in foliar pathogens are still elusive. In this study, we cloned the gene Stgg1 encoding G protein γ subunit in Setosphaeria turcica and investigated its function by RNA interference technology. Three independent Stgg1 targeted RNAi mutants R3, R5 and R6 with diverse silencing efficiency were generated. Knock-down of Stgg1 resulted in a significant reduction in mRNA levels of the genes encoding Gα (Stga1, Stga2, Stga3) but not for Gβ (Stgb1). Stgg1 RNAi mutants exhibited significantly elongated hyphal cells with blocked conidium production. In addition, Stgg1 RNAi mutants all appeared in lighter colony colour compatible with inhibited secondary metabolites. Further assays demonstrated that Stgg1 was required for biosynthesis of melanin and HT-toxin activity. Furthermore, down-regulation of Stgg1 largely inhibited the inflection capacity. Thus, we proposed that Stgg1 played crucial roles in conidiation, secondary metabolite production and pathogenicity of S. turcica and is, therefore, an ideal target for drug design against foliar pathogens.